Development of Blended Learning-Based Family Institution Partnership Model in Stimulating Early Children's Development - Rahma, Rezka Arina; Rahmania, Lidya Amalia; Sari, Zihan Novita (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
This study aimed to develop a partnership model between Early Childhood Education (PAUD) institutions and families based on blended learning and to test the partnership model's effectiveness in stimulating children's development. The research and development (R&D) method is used in this research. This study develops a blended learning-based partnership model between the Institute and the family and tests the model's effectiveness in stimulating children's development. The research subjects were principals, teachers, administrators, and parents at TPA Melati Dharma Wanita Persatuan UM. The results showed that the factual partnership model becomes a reference in developing the school's partnership model with parents through the blended learning method. This factual model includes planning, organizing, implementing, and evaluating the school's partnership program with parents. Through the blended learning method, the school partnership model with parents can help TPA Melati UM develop and implement a school partnership program with parents, which must be adapted to school conditions. It is the objective of School-Based Quality Improvement Management (Manajemen Peningkatan Mutu Berbasis Sekolah-MPMBS). Factors that influence the effectiveness of the blended learning model include the basic requirements of the model, the profile, roles and characteristics of the school, and monitoring and evaluation.